Analisis Kapasitas Saluran Sistem Drainase di Simo Katrungan Kidul Sawahan Surabaya - Nusantara, Danayanti Azmi Dewi (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
Sawahan is a densely populated sub-district located in the city of Surabaya with a population density which until 2017 reached 215,024 people as a result of a wide and deep drainage channel which became narrow and shallow as more and more settlements developed. And when the rainy season comes, the drainage channel in the Banyu Urip (Simo Katrungan Kidul) area of Surabaya is unable to collect rainwater, causing water overflow in the drainage and flood channels. Heavy rain for more than 1.5 hours and hit Simokatrungan area can cause inundation up to 500 meters inundated. The deepest puddles reach the knees of adults or about 60 cm. The purpose of this study is how to calculate flood discharge and channel dimension planning for the next 2022 planning year. The methods used are hydrological analysis, Existing channel analysis, flood discharge analysis for the next 2 years (2022), and channel capacity for 2022.Based on capacity analysis Secondary Channel Simo Katrungan Kidul Eastern Section is 0.003 m3 / s, while the existing design debit is 0.126 m3 / s, the channel cannot accept the design debit. So the dimensions for this channel are planned to form trapezoidal b1 = 1.3 m. b2 = 1.8 m, h = 1 m. The Northern Tertiary Simo Katrungan Kidul channel capacity is 0.031 m3 / sec, while the existing design discharge is 0.096 m3 / sec. So that the dimensions for this channel are planned to form trapezoid b1 = 1.6 m, b2 = 2.2 m, h = 1.2 m. Simo Katrungan North Section Secondary channel capacity is 0.002 m3 / sec, while the existing design discharge is 0.360 m3 / sec. So that the dimensions for this channel are planned to form trapezoid b1 = 1.6 m, b2 = 2.2 m, h = 1.2 m.